Incidencia del síndrome diarreico agudo por exámen coprológico y coproparasitario complementado con una biometría hemática completa en niños menores de 4 años en el Hospital Teófilo Dávila del año 2014 - Guerrero Jiménez, Carmen Victoria (2015)
The acute diarrhea remains one of the major health problems of humanity and a scourge to the immensity of the children living in third world countries. The World Health Organization defines a case of diarrhea as removing three or more loose or liquid over a period of 24 hours BM.